Understanding online impulse buying in China’s live e-commerce: the role of key opinion leaders and perceived trust - Cai, Shuang; Ambad, Sylvia Nabila Azwa (Universiti Teknologi MARA, Perlis, 2025)
In the current environment where live-streaming e-commerce is booming, creating key opinion leaders has become a very common and effective marketing strategy. Perceived trust, as an important antecedent factor influencing consumers' purchasing behavior, deserves more exploration. This study examines the impact of key opinion leaders on the live-streaming e-commerce industry in China, with a focus on the interaction and expertise dimensions of key opinion leaders and their influence on consumers' impulse buying behavior. A quantitative research method was adopted, and data were collected through a questionnaire survey on Questionnaire Star forms. The survey participants were users of Douyin, Kuaishou, and Taobao Live aged between 18 and 34, currently residing in Guangxi, Jiangxi, and Henan provinces in China. The existing measurement items were adjusted accordingly for the live-streaming e-commerce industry, and the data were analyzed using SmartPLS 4.0. The results show that perceived trust has a significant mediating effect between the professionalism of key opinion leaders and consumers' online impulse buying behavior, while the interaction of key opinion leaders does not have a mediating effect. This might be because the real-time interaction between key opinion leaders and consumers may directly stimulate impulsive consumption through non-trust paths, such as emotional arousal, presence, or social identity, bypassing the trust evaluation stage and directly triggering impulsive behavior. This study provides valuable insights for the live-streaming e-commerce industry.